Mac OS X Snow Leopard for Power Users - Granneman, Scott (Apress, 2012)
The title of this book is Mac OS X Snow Leopard for Power Users. So what’s a Power User? Why should power users be interested in Mac OS X, an operating system famed for its ease-of-use? And what will power users learn in this book?